Association of prolonged ECMO bridging and perioperative factors with dysphagia and survival after lung transplantation - Woo Chul Son; Garam Hong; Sang-Bum Hong; Cheon Ji Kang; Ho Cheol Kim; Won Kim (PLoS ONE, 2026)
Objectives To evaluate the association between perioperative variables, including extracorporeal membrane oxygenation bridge-to-transplantation (ECMO BTT), and the development of dysphagia after lung transplantation (LT), and to examine the association between postoperative dysphagia and long-term survival. Methods This retrospective, single-center study included adult patients who underwent LT between November 2008 and December 2022. Swallowing function was assessed using the Functional Oral Intake Scale (FOIS) on postoperative day (POD) 28, POD 60, and at hospital discharge. Patients were classified into dysphagia (FOIS ≤3) and non-dysphagia (FOIS >3) groups based on FOIS at POD 28. Perioperative variables associated with dysphagia were examined using multivariable logistic regression. Survival outcomes were assessed using Kaplan–Meier analysis. Results Among the 124 included patients, 35.9% had dysphagia at POD 28, whereas 87.1% achieved functional oral intake by hospital discharge. Prolonged ECMO BTT (≥14 days), tracheostomy before POD 28, female sex, and postoperative pneumonia were independently associated with dysphagia at POD 28. Patients with dysphagia at POD 28 showed significantly poorer unadjusted 1-year and 2-year survival than those without dysphagia. Conclusions Dysphagia at POD 28 after LT was associated with prolonged ECMO BTT, tracheostomy before POD 28, postoperative pneumonia, and poorer unadjusted survival. FOIS at POD 28 may serve as a clinically meaningful marker of delayed recovery and increased clinical vulnerability.